Development of graphic skills in the process of doing the prints on plastic at lessons in the field of supplementary education - Semina V. V. (Interactive science, 2016)
the authors of the follwing paper mark that students have great difficulties in creating the prints on plastic in case they don’t master the basic skills. Without obtaining the techniques, it is difficult for children to recognise this techniques themselves so it is very important to perform exercises.
Keywords: упражнения; методика обучения; exercises; methods of teaching; гравюра на пластике; engraving on plastics